1973
DOI: 10.1017/s002217240004626x
|View full text |Cite
|
Sign up to set email alerts
|

The post-mortem diagnosis of influenzal infection by fluorescent IgG, IgA and IgM antibody studies on necropsy blood

Abstract: SUMMARYNecropsy blood from cases diagnosed as dying from influenza A was examined for specific antibody in the IgG, IgA and IgM fractions and a specific diagnosis of recent infection was made if either 1gM or IgA antibody and low titres of IgG antibody were found. By these criteria a diagnostic rate of 77 % was found in those cases from whom no virus was isolated. The use of infected cell monolayers grown on polytetrafluoroethylene-coated slides gave a simple method of carrying out these antibody assays, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…DE SILVA et cd. (7) have previously demonstrated that a serological diagnosis of recent influenza is possible post mortem.…”
Section: Discussionmentioning
confidence: 99%
“…DE SILVA et cd. (7) have previously demonstrated that a serological diagnosis of recent influenza is possible post mortem.…”
Section: Discussionmentioning
confidence: 99%
“…have previously been demonstrated by immunofluorescence procedures in the sera of patients recently infected with influenza virus (De Silva et al, 1973;Urquhart, 1974). However, using immuno-fluorescence, Brown and O'Leary (1973) found that, in naturally infected individuals all the specific influenza antibody with IgM specificity was of the 7S type.…”
Section: Specific 1gm Antibodies Against Influenza Virusesmentioning
confidence: 95%
“…Specific IgM has been detected after recent natural infection with influen2a A virus by haemagglutination-inhibition following gel chromatography (Dobrovolskaya, 1971), radioimmunoassay (Daugharty et al, 1972), and immunofluorescence (Brown and O'Leary, 1973;De Silva et al, 1973;Urquhart, 1974). However, although specific IgM of the 19S class has been found by some workers (Dobrovolskaya, 1971;Daugharty et al, 1972) such specific IgM has been found to be exclusively of the 7S type by others (Brown and O'Leary, 1973).…”
mentioning
confidence: 99%